PEWARNA ALAMI BATIK DARI KULIT SOGA TINGI (Ceriops tagal) DENGAN METODE EKSTRAKSI - Handayani, Prima Astuti; Maulana, Ivon (Semarang State University, 2013)
Synthetic coloring techniques shift the natural coloring techniques because the process is much easier, and the resulting color is more diverse. However, it comes into doubts if the synthetic color materials is continuously used because the produced waste harms the human health and indirectly polutes the environment. Hence, the bark of soga tingi which contains tanin as natural coloring subtances can be used as a substitute for synthetic dyes for Batiks. The extraction of tanin from the soga tingi bark is carried out in the refluxed equipment set. The materials used in the study consist of ethanol, aquadest, soga tingi bark, alum, lime, and tunjung. The experiment is done by varying the solvents and the extraction time. The solvent of ethanol-aquadest used in the experiment varied at the ethanol concentration of 96%, 70%, 30%, and without ethanol. The bark of soga tingi is dried and crushed into powder. The ratio of materials and solvent used in the experiment is 1:4 m/v. The extraction run at temperature of 700 oC for 3 hours. The coloring substances is subsequently analyzed by UV-Vis spectrophotometry. The coloring substances made of soga tingi bark is applied by adding other key components such as alum, lime, and tunjung. The experimental results show the extraction of tanin from soga tingi bark yield the highest tanin (24,343 ppm) when solvent of 96% ethanol is used. Moreover, the extraction for 3 hours yield higher tanin concentration than 2 hours. This dye has been applied on the fabric using 3 types of key substances. To the key substances in form of tunjung produce black color, lime produces a brown color, and alum produces a reddish-brown color.